Respuesta :

Answer: (-6,-9)

Step-by-step explanation: you probably don't wanna read this but in case someone asks you about it- first start by putting the first equation into graphing form, turning it into 2y=-3x+12.

then you can go ahead and multiply the second equation by two to get 2(y=1/2x-6), which is 2y=x-12.

next, just subtraction! 2y=-3x+12 minus 2y=x-12!

You get -4x=24, which leaves you to divide both sides by -4 to get x=-6!

now to put in x for the solution, you take a equation(either one) and put in x

[y=1/2(-6)-6]

[y=-3-6]

[y=-9]

so your points are (-6,-9)

ACCESS MORE